ANALISIS FINANSIAL USAHATANI PADI ( Oryza sativa L) PADA LAHAN PASANG SURUT TIPE B DI DESA BUNIPAH KECAMATAN ALUH-ALUH KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Yayuk Minta Wahyuningsih; Zuraida Zuraida (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
The purpose of this research is to know Revenue, Profit, Capital Productivity, Manpower Distribution and Feasibility of Typhoon Type B Farming in Bunipah Village, Aluh-Aluh Sub-District, Banjar District of South Kalimantan Province. Method of Village Research using Purposive Sampling and for Sampling of Farmers by using Random Sampling sampling that is taken 10% from population amount of 190 tidal rice farmer type B, so obtained 19 farmer sampel.Dan for Revenue Data = TR-TEC, Profit = TR-TC, Capital Productivity = Profit divided by total cost x 100%, Labor Distribution = Total cost of Labor divided by Total cost x 100% whereas Feasibility = TR / TC. The results showed that Average Tidal Rice of Type B tidal land is Rp 9.076.711 farming. with Average Profit is Rp 7,518,879 / farmer and Average Capital Productivity equal to 85,04%, Average outside Labor Distribution equal to 69,88% and average inside labor distribution equal to 34,94% with Average Feasibility of Field Farming of Type Surface Ms Type 1, 85 means Types of Tidal Wetland Farming Type B is feasible to cultivate.